1999
DOI: 10.1111/j.1349-7006.1999.tb00703.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Analysis of Adenosquamous Carcinoma of the Lung

Abstract: Adenosquamous carcinoma of the lung is a subset of pulmonary carcinomas, and comprises less than 4% of lung carcinomas. Its histogenesis remains unclear. The clonality of adenosquamous carcinoma from four female patients was analyzed to determine whether the clonality between the squamous cell and adenocarcinomatous components coincides. Each lesion was precisely microdissected from methanol-fixed sections. Adjacent normal lung tissue was collected as a normal control. DNA was extracted for clonal analysis bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…Nkx2-1 deletion promotes lung ADC to transdifferentiate towards gastric lineage 34 . Consistently, clinical studies have found convergent mutations in both ADC and SCC components from a single lesion of human Ad-SCC [35][36][37][38][39] , leading to the hypothesis that there exists dynamic cell lineage conversion between these two pathologically and morphologically distinct tumour subtypes. Our work in Lkb1-deficient mouse models has recently provided the first de novo evidences supporting this hypothesis 18 .…”
Section: Discussionmentioning
confidence: 73%
“…Nkx2-1 deletion promotes lung ADC to transdifferentiate towards gastric lineage 34 . Consistently, clinical studies have found convergent mutations in both ADC and SCC components from a single lesion of human Ad-SCC [35][36][37][38][39] , leading to the hypothesis that there exists dynamic cell lineage conversion between these two pathologically and morphologically distinct tumour subtypes. Our work in Lkb1-deficient mouse models has recently provided the first de novo evidences supporting this hypothesis 18 .…”
Section: Discussionmentioning
confidence: 73%
“…Thus, dierent animals or dierent breasts in the same animal developed independently invasive tumors with a predominating solid, nodular form that possibly evolved into a few variants, including a pattern of adenoacanthomatous metaplasia. Although adenosquamous carcinomas developing in the breast or in other organs are rarely observed in humans (see, for example, Denley et al, 2000), it is interesting to note that independent molecular analyses of lung tumors have suggested that the squamous and adenocarcinomatous components had originated from the same cell (Niho et al, 1999;Kanazawa et al, 2000).…”
Section: Tumor Pathogenesis In the Absence Of Brca2mentioning
confidence: 99%
“…To our knowledge, 2 reports have also described the monoclonality of 2 components in adenosquamous carcinoma by genetic analysis. 10,11 Immunohistochemical analyses have indicated that the protein expression characteristics of the adenocarcinomatous and squamous cell carcinomatous components differ. 3,9,11 Taking together these findings, the tumorigenesis in some population of adenosquamous carcinoma is hypothesized; the critical event causing oncogenesis, such as a mutation in K-ras or EGFR, occurs in the progenitor cells of the adenosquamous carcinoma, then, in the process of multistep tumorigenesis, subsequent differences in the protein expression profiles may cause the cells to differentiate into 2 different phenotypes.…”
Section: Dear Sirmentioning
confidence: 99%
“…[10][11][12] In our study, we investigated the molecular features of adenosquamous carcinoma, a typical heterogeneous tumor of the lung.…”
Section: Dear Sirmentioning
confidence: 99%
See 1 more Smart Citation